Tibetan Medicine for Diabetes Mellitus: Overview of Pharmacological Perspectives - Yan, Li-Shan; Cheng, Brian Chi-Yan; Zhang, Shuo-Feng; Luo, Gan; Zhang, Chao; Wang, Qing-Gao; Fu, Xiu-Qiong; Wang, Yi-Wei; Zhang, Yi (Frontiers in Pharmacology, 2021)
Diabetes mellitus (DM) and its complications pose a major public health threat which is approaching epidemic proportions globally. Current drug options may not provide good efficacy and even cause serious adverse effects. Seeking safe and effective agents for DM treatment has been an area of intensive interest. As a healing system originating in Tibet, traditional Tibetan medicine (TTM) has been widely used by Tibetan people for the prevention and treatment of DM and its complications for hundreds of years. Tibetan material medicamedicines (TMM) including the flower of Edgeworthia gardneri (Wall.) Meisn., Phyllanthi Fructus, Chebulae Fructus, Huidouba, and Berberidis Cortex are most frequently used and studied. These TMMs possess hypoglycemic, anti-insulin resistant, anti-glycation, lipid lowering, anti-inflammatory, and anti-oxidative effects. The underlying mechanisms of these actions may be related to their α-glucosidase inhibitory, insulin signaling promoting, PPARs-activating, gut microbiota modulation, islet β cell-preserving, and TNF-α signaling suppressive properties. This review presents a comprehensive overview of the mode and mechanisms of action of various active constituents, extracts, preparations, and formulas from TMM. The dynamic beneficial effects of the products prepared from TMM for the management of DM and its complications are summarized. These TMM are valuable materia medica which have the potential to be developed as safe and effective anti-DM agents.